EFEKTIVITAS LARUTAN BAWANG PUTIH DALAM MEMBUNUH LARVA Aedes aegypti - Dwi Sulistyoningsih; Budi Santosa; Didik Sumanto (JURNAL KESEHATAN, 2009)
Abstract Background: Garlic is also used as a spice in cooking are also used as traditional medicine. Garlic is usually used for treatment of worms being able to apple worms Because the content of garlic is dried, the possibility of garlic can kill mosquito larvae. The purpose of this study was to measure the fictiveness of –garlic so-lotion killing the larvae of Aedes aegtpti, and to know different number of dead larvae of various concentrat ions of gar lic s olut ion.   Methode: This type of research is conducted experiments in the laboratory of miuobiologt, Faculty of Health Sciences and Nursing, UJniversity of Muhammadiyah Semarang. The sample used was the Aedes  mosquito larvae to instor-4 obtained from Vector Reservoir Development Center of Disease (BPVRP) Salatiga. Direct examination conducted by mixing the garlic extract with water in certain concentrations, so get thi g,arlic solution which was then at each concentration of garlic solution Aedes aegtpti larvae included as many as l0 tails. Research resulls. At t% concentrations can not be ffictive because the number of dead larvae less than 75o/o. Whereas the concentration of 5o%, l0%,25% and 50% could e/fictively kill The larvae because of the number of dead larvae is greater than or equal to 75o%' Conclusions: The lowest concentration of garlic solution that can kill the larvae of Aedes aegtpti is a concentration of 5%o and there are differences in the overage number of Aedes aegepti larvae mortality of garlic solution with various concentrations. Keywords: garlic, Aedes aegtpti larvae